Pengaruh Implementasi Game Duolingo terhadap Kemampuan Linguistik pada Siswa - Dendi Juniansyah; Fikry Kurniawan; Syarifuddin Syarifuddin (Departement of Mathematics Education, 2024)
The rapid development of technology encourages the emergence of the latest innovations in various aspects of human life, including education. One popular innovation in education is the use of gamification-based educational applications. This application is packaged in an interesting and interactive way, like a game, for example, the duolingo game. The duolingo game is an application that presents language learning materials in the form of interactive and fun games or challenges. Apart from being an educational game, this duolingo application can also improve linguistic abilities in students. This study aims to determine the effect of the application or implementation of the duolingo game on linguistic abilities in students. The research method uses a descriptive qualitative approach by collecting literature related to the title of the study or discussion taken. From the research that has been done, the results show that the implementation of the duolingo game has a significant positive effect on students' linguistic abilities, and can increase students' enthusiasm or enthusiasm for learning.